2021
DOI: 10.1186/s12870-021-02824-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of wheat near-isogenic lines reveals candidate genes on chromosome 3A for pre-harvest sprouting resistance

Abstract: Background Pre-harvest sprouting (PHS) in wheat can cause severe damage to both grain yield and quality. Resistance to PHS is a quantitative trait controlled by many genes located across all 21 wheat chromosomes. The study targeted a large-effect quantitative trait locus (QTL) QPhs.ccsu-3A.1 for PHS resistance using several sets previously developed near-isogenic lines (NILs). Two pairs of NILs with highly significant phenotypic differences between the isolines were examined by RNA sequencing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…RNA was extracted with the method described previously, and three biological replications in two separate wells (technical replication) were applied. The cDNA was synthesized by SensiFAS cDNA Synthesis Kit (Meridian Bioscience, United States), and qRT-PCR was performed on ABI 7500 Fast Real Time PCR (Applied Biosystems, CA, United States) using the SensiFAST SYBR Lo-ROX Kit (Meridian Bioscience, United States), following methods described by Wang et al (2021) . The relative fold changes were calculated using the comparative CT method (2 –ΔΔCT ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted with the method described previously, and three biological replications in two separate wells (technical replication) were applied. The cDNA was synthesized by SensiFAS cDNA Synthesis Kit (Meridian Bioscience, United States), and qRT-PCR was performed on ABI 7500 Fast Real Time PCR (Applied Biosystems, CA, United States) using the SensiFAST SYBR Lo-ROX Kit (Meridian Bioscience, United States), following methods described by Wang et al (2021) . The relative fold changes were calculated using the comparative CT method (2 –ΔΔCT ).…”
Section: Methodsmentioning
confidence: 99%
“…NILs with identical genetic backgrounds, except for one or a few genetic locus/loci of interest, minimize the interference of the genetic background and enhance the sensitivity and accuracy of transcriptional analysis ( Yan et al, 2017 ; Mia et al, 2019 ). The combined use of NILs with RNA-seq analysis was successfully used to identify resistance conferring genes, underpinning the QTL for important quantitative traits such as Fusarium crown rot, pre-harvest sprouting, and heat and drought stress in wheat ( Ma et al, 2014 ; Schmidt et al, 2020 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PrimerQuest tool (https://sg.idtdna.com) was used for gene‐specific (exon–exon junction) primer design. The total RNA was reverse‐transcribed in a 20 μL reaction system by SensiFAST cDNA Synthesis Kit (Meridian Bioscience) and used for real‐time polymerase chain reaction (qRT‐PCR) on ABI 7500 Fast Real‐Time PCR (Applied Biosystems, Waltham, CA, USA) (Wang et al., 2021). The reactions were performed in 96‐well plates with a 25 μL reaction mixture (in each well) containing 10 μL SensiFAST SYBR Lo‐ROX (Meridian Bioscience).…”
Section: Methodsmentioning
confidence: 99%
“…Because proteins are involved in plant stress responses, proteomic studies can lead to an understanding of the possible relationships between protein changes and plant stress tolerance (S. Wu et al, 2017). Near‐isogenic lines (NILs) are lines with identical genetic backgrounds except for a few specific locations that are used to minimize genetic background effects such as epistatic interactions (Wang et al., 2021). Thus, the comparison of the proteome in drought‐tolerant and susceptible isolines can be used in understanding the underlying mechanism of the targeted locus responsible for drought tolerance (Michaletti et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since PHS causes yield losses, adversely impacts grain quality, and leads to a large economic loss in rice production worldwide, significant attention has been devoted to investigating the molecular mechanisms of PHS tolerance for breeding PHS-resistant rice varieties. Numerous studies in different plant species have concluded that PHS resistance is highly quantitative and controlled by many quantitative trait loci [ 22 24 ]. In rice, accumulating studies indicate that many characterized genes that participate in PHS regulation are mainly involved in ABA biosynthesis, catabolism, and signalling.…”
Section: Introductionmentioning
confidence: 99%